Islamisation and the formation of vernacular Muslim material culture in 15th-century northern Sumatra. Issue 143 (2nd January 2021) - Feener, R. Michael; Daly, Patrick; Edwards McKinnon, E.; En-Ci, Luca Lum; Ardiansyah,; Nizamuddin,; Ismail, Nazli; Seng, Tai Yew; Rahardjo, Jessica; Sieh, Kerry
ABSTRACT: This study presents a distinctive type of Muslim gravestone found on the northern coast of Sumatra, Indonesia, that dates to the 15th century. These grave markers, locally known as plang-pleng, provide evidence for the formation and disappearance of an early form of vernacular Muslim material culture in Southeast Asia. We documented over 200 of these gravestones during a large-scale archaeological landscape survey. In this article, we present a typology of these gravestones based upon shape, morphology and ornamentation. We then discuss their geographical distribution and periodisation based on examples with dated Arabic inscriptions. Our results show that these gravestones were initially a cultural product of the historic trading settlement of Lamri dating from the early 15th century. By the middle of the 15th century, variations of these stones started to appear widely near the Aceh river. The plang-pleng tradition was displaced in the early 16th century by the batu Aceh gravestones associated with the Aceh sultanate, which became a standardised part of Muslim material culture in the region for the next two centuries.